Behavior of Composite Steel Deck-Concrete Slabs Subjected to Elevated Temperature - A. Waryosh, Waleed; Hassan Daiyr Al-Aubadi, Ahmed (Journal of Engineering and Sustainable Development, 2009)
The present study is concerned with the behavior of composite steel deck-concrete slabs under the effect of high temperature. Twenty-eight slabs were prepared for this matter and divided into eight groups. The parameters included in this study are slab depth, additional reinforcement (reinforcing bars, welded wire mesh, transverse spot-welded wires), and temperature level. The specimens were tested as simply supported slabs with the two-point load. The ultimate load capacity, mid-span deflection, slip at ends of slab, failure mechanism, and crack pattern are studied. The ultimate load capacity for composite slabs decreases significantly when subjected to high temperatures. The decrease in the ultimate load capacity becomes less when additional reinforcement is used in composite slabs.